2015
DOI: 10.1111/ppl.12337
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of a salt‐inducible TaSR gene in Triticum aestivum

Abstract: The gene expression chip of a salt-tolerant wheat mutant under salt stress was used to clone a salt-induced gene with unknown functions. This gene was designated as TaSR (Triticum aestivum salt-response gene) and submitted to GenBank under accession number EF580107. Quantitative polymerase chain reaction (PCR) analysis showed that gene expression was induced by salt stress. Arabidopsis and rice (Oryza sativa) plants expressing TaSR presented higher salt tolerance than the controls, whereas AtSR mutant and RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The LRR motif plays a central role in recognizing different pathogen-associated molecules in the innate host defense of plants and animals [47]. Recent studies have shown that several genes encoding LRR-containing proteins are involved in the abiotic stress response [48], including LP2 ( LEAF PANICLE 2 ), TaPRK2697 ( Triticum aestivum PROTEIN OF RECEPTOR KINASES 26697 ), AtPXL1 ( Arabidopsis thaliana PHLOEM INTERCALATED WITH XYLEM-LIKE 1 ), and LRR-RLK-VIII ( LEUCINE-RICH REPEAT RECEPTOR-LIKE KINASE VIII ), which are upregulated by drought, salt, cold, and toxic metals, respectively, in diverse plant species [49,50,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The LRR motif plays a central role in recognizing different pathogen-associated molecules in the innate host defense of plants and animals [47]. Recent studies have shown that several genes encoding LRR-containing proteins are involved in the abiotic stress response [48], including LP2 ( LEAF PANICLE 2 ), TaPRK2697 ( Triticum aestivum PROTEIN OF RECEPTOR KINASES 26697 ), AtPXL1 ( Arabidopsis thaliana PHLOEM INTERCALATED WITH XYLEM-LIKE 1 ), and LRR-RLK-VIII ( LEUCINE-RICH REPEAT RECEPTOR-LIKE KINASE VIII ), which are upregulated by drought, salt, cold, and toxic metals, respectively, in diverse plant species [49,50,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…These two abiotic stressors have been fundamentally linked to plant hormonal pathways, which is abscisic acid (ABA), a plant phytohormone designated as a key regulator in the activation of osmotic stress-responsive genes upon drought and salinity conditions [58][59][60]. Additionally, there are several leucine-rich repeat receptor like-kinases (LRR-RLKs) that have been proven to be involved in the response to drought-and salinity-activated ABA signaling pathways, however, most of them are localized at the PM compartment [61][62][63][64][65][66][67][68]. A recent report showed that two LRR-RLKs of Arabidopsis thaliana, QSK1 (Qian Shou kinase) and IMK2 (inflorescence meristem kinase 2) localized in the PM upon the normal condition, but this PM-located QSK1/IMK2 is phosphorylated and subsequently relocalized at PD-PM channels in response to salt and mannitol treatments [32].…”
mentioning
confidence: 99%
“…Another salt tolerance gene isolated from a salt tolerant wheat mutant is TaSR. Overexpressing this gene in rice and Arabidopsis increased the Na + secretion and led to increased intracellular K + and Ca 2+ concentrations, thereby increasing salt tolerance in two glycophyte species (Ma et al, 2016). Another interesting transporter is a Na + pumping ATPase, called PpENA1, that was found in moss.…”
Section: Saline Agriculturementioning
confidence: 99%